Differences in the suppression of distortion product otoacoustic emissions by contralateral white noise between patients with acute or chronic tinnitus. (3rd August 2017) - Riga, Maria; Komis, Agis; Marangoudakis, Pavlos; Naxakis, Stefanos; Ferekidis, Eleftherios; Kandiloros, Dimitrios; Danielides, Vasilios
Abstract: Objective : The mechanisms underlying the shift from acute tinnitus to chronic remain obscure. An association between tinnitus and medial olivocochlear bundle (MOCB) reflex dysfunction has been hypothesised by several studies. The differences between participants with acute and chronic tinnitus have not yet been investigated. Design : Participants were examined with distortion product otoacoustic emissions (DPOAEs) suppression elicited by contralateral white noise. They were compared in terms of frequency regions with non-recordable DPOAEs, suppression amplitudes and the presence of DPOAE enhancement. Study sample : Eighteen participants with acute tinnitus, 40 age-matched adults with chronic tinnitus and 17 controls were included. All participants (aged 34.7 ± 9.6years; mean ± Standard deviation) had normal hearing. Tinnitus was bilateral in 22 participants and unilateral in 36. Results : Ears with chronic tinnitus presented significantly lower DPOAE suppression amplitudes than ears with acute tinnitus ( p < 0.0001). Both acute and chronic tinnitus ears present a high prevalence of enhancement, significantly different from controls ( p < 0.0001, p = 0.0002, respectively). Non-recordable DPOAEs were significantly more frequent in the chronic than in the acute tinnitus and control groups ( p < 0.0001). Conclusions : The differences between study groups indicate that when tinnitus becomes chronic, DPOAEs suppression presents changes that might reveal corresponding steps in tinnitus pathophysiology. Treatment implications are discussed.